The art of we happy few ebook - Compulsion Games (Dark Horse Comics, LLC., 2018)
The official art book to the game! Two-hundred pages of mind-bending art and insightful creator commentary exploring the conceptualization and execution of We Happy Few! October, 1964. The City of Wellington Wells is all that's left of England after the German invasion and four years of occupation. But it's still the swinging '60s, and everyone is fab, especially because they're taking happy pills--Joy--and wearing Happy Face masks so they're always smiling . . . everyone except the awful Downers who live in the abandoned Garden District and refuse to take their Joy. Dark Horse Books and Compulsion Games are thrilled to present The Art of We Happy Few. Showcasing a unique retro-futuristic style, this book includes hundreds of pieces of concept art, paired with exclusive commentary from the team that created it! Don't be a Downer by missing out on this perfect companion to the psychedelic videogame experience!